a) -1 ×(-6,2 + 4,3 - 3,8 + 5,7 - 8)=

b)-1×(4,8 - 1,2 + 7,3 - 4,5 - 6)=

C)-2 ×(14,1 + 19,6 - 20,8 - 16,7)=
plis zrubcie


Odpowiedź :

a) -1x(-6,2+4,3-3,8+5,7-8)=6,2x-4,3x+3,8x-5,7x+8x= 8x
b)-1×(4,8 - 1,2 + 7,3 - 4,5 - 6)=-4,8x+1,2x-7,3x+4,5x+6x= -0,4x

c)-2 ×(14,1 + 19,6 - 20,8 - 16,7)=-28,2x-39,2x+41,6x+33,4x= 7,6x
a) = -1 × (-8.1)=8.1
b)=-1 × (0.4)= -0.4
c)=-2 × (-3.8)=7.6

Proszę
a) -1×(-6,2 + 4,3 - 3,8 + 5,7 - 8)= 6,2x - 4,3x + 3,8x - 5,7x + 8x = 8x
b)-1×(4,8 - 1,2 + 7,3 - 4,5 - 6)= -4,8x + 1,2x - 7,3x + 4,5x + 6x = -0,4x
c)-2×(14,1 + 19,6 - 20,8 - 16,7)= -28,2x - 39,2x + 41,6 + 33,4x = 86x